Rapid detection of Staphylococcus aureus in food safety using an RPA-CRISPR-Cas12a assay. (March 2023) - Lin, Liyun; Zha, Guangcai; Wei, Huagui; Zheng, Yuzhong; Yang, Peikui; Liu, Yaqun; Liu, Mouquan; Wang, Zhonghe; Zou, Xianghui; Zhu, Hui; Luo, Qiulan; Li, JinQuan; et al.
Abstract: At present, the main challenge for Staphylococcus aureus ( S. aureus ) in food safety is still a lack of rapid, convenient detection methods. This study developed a combination of recombinase polymerase amplification (RPA) and the CRISPR-Cas12a technology (known as the RPA-CRISPR-Cas12a assay) for the detection of S. aureus in food. This novel assay could detect samples with a fluorescence reader, lateral flow dipstick (LFD) or the naked eye under a UV transilluminator. After optimization, the RPA-CRISPR-Cas12a assay could specifically and stably detect S. aureus as low as 1–10 copies/μL within 40 min at 37 °C. This assay had high sensitivity to the detection of S. aureus in both laboratory standard samples and field samples, which indicated the feasibility of this assay. To sum up, this accurate, portable detection method for S. aureus has great potential applications in food safety, especially in the field, without requiring sophisticated equipment or high level of technical expertise.